First Report of Tomato leaf curl New Delhi virus Infecting Cucurbits in the Canary Islands - Espino-De-Paz, A. I.; Botella-Gillén, M.; Otazo-González, H. C.; Alfaro-Fernández, Ana; Font-San-Ambrosio, Isabel; Galipienso, Luis; Rubio, Luis (APS (The American Phytopathological Society), 2020)
Tomato leaf curl New Delhi virus (ToLCNDV), a member of the genus Begomovirus, is transmitted by the whitefly Bemisia tabaci in a persistent mode and cause considerable yield losses in several solanaceous and cucurbitaceous crops. ToLCNDV was first detected in tomato (Solanum lycopersicum) in India and spread to other Asian countries infecting members of the families Solanaceae and Cucurbitaceae (Moriones et al. 2017). Recently, this virus emerged in cucurbit crops in peninsular Spain (Juárez et al. 2014) and spread rapidly to other western Mediterranean countries: Tunisia (Mnari-Hattab et al. 2015), Italy (Panno et al. 2016), and Morocco (Sifres et al. 2018), being included in the alert list of the European and Mediterranean Plant Protection Organization (EPPO). In spring 2018, melon (Cucumis melo), zucchini (Cucurbita pepo), and squash (Cucurbita maxima) plants showing symptoms characteristic of ToLCNDV infection (curling and mosaic in young leaves, short internodes, and stunting) were observed in several municipalities in Gran Canaria, the Canary Islands. Twenty-five plants (four symptomatic and two asymptomatic melon, six symptomatic and two asymptomatic zucchini, and nine symptomatic and two asymptomatic squash plants) were analyzed with ImmunoStrip for ToLCNDV (Agdia Inc.) and only the symptomatic plants yielded a positive reaction. These results were confirmed by PCR with specific primers to ToLCNDV: A2-F/A3-R (Ruiz et al. 2015). PCR products of the expected size (1,260 bp) were obtained only from the symptomatic plants and the nucleotide sequences of these ToLCNDV isolates from Gran Canaria were almost identical irrespective of the host (nucleotide sequence identities ≥99.7%). The complete DNA-A and DNA-B genomic segments of a ToLCNDV isolate from zucchini were sequenced and deposited in GenBank under accessions numbers MK382392 and MK382393. Nucleotide sequence identities were calculated with SDTv1.2 (Brown et al. 2015) showing that these sequences shared the closest relationship to sequences from ToLCNDV isolates from peninsular Spain and Morocco (>99.0%) and Italy (>98.0%), whereas they differed from ToLCNDV isolates from Asia (∼90% for DNA-A and ∼82% for DNA-B). Tests conducted by PCR with conserved primers for begomoviruses (Briddon and Markham 1994; Lecoq and Desbiez 2012) did not detect any other begomoviruses and tests by PCR with conserved primers for DNA satellites (Briddon et al. 2002; Bull et al. 2003) were negative. This is the first report of ToLCNDV in the Canary Islands. The emergence of this virus poses a threat to the cucurbit crops of Gran Canaria island and requires measures to prevent the spread of ToLCNDV in this island and to the other islands.